Developing an Adjunct Services Approach to Identify the Use of Procedures Not Covered by Health Insurance: The Case of In Vitro Fertilization. Issue 4 (10th April 2023) - Hirth, Richard A.; Levinson, Zachary M.; Blattner, Neha Buch; Dalton, Vanessa K.; Kelley, Angela S.; Lanham, Michael; Manning, Marsha; Norton, Edward C.; Levy, Helen G.; Dupree, James M.
Abstract : Background: Health care claims have an inherent limitation in that noncovered services are unreported. This limitation is particularly problematic when researchers wish to study the effects of changes in the insurance coverage of a service. In prior work, we studied the change in the use of in vitro fertilization (IVF) after an employer added coverage. To estimate IVF use before coverage began, we developed and tested an Adjunct Services Approach that identified patterns of covered services cooccurring with IVF. Methods: Based on clinical expertise and guidelines, we developed a list of candidate adjunct services and used claims data after IVF coverage began to assess associations of those codes with known IVF cycles and whether any additional codes were also strongly associated with IVF. The algorithm was validated by primary chart review and was then used to infer IVF in the precoverage period. Results: The selected algorithm included pelvic ultrasounds and either menotropin or ganirelix, yielding a sensitivity of 93.0% and specificity of >99.9%. Discussion: The Adjunct Services Approach effectively assessed the change in IVF use postinsurance coverage. Our approach can be adapted to study IVF in other settings or to study other medical services experiencing coverage changes (eg, fertility preservation, bariatric surgery, and sex confirmation surgery). Overall, we find that an Adjunct Services Approach can be useful when (1) clinical pathways exist to define services delivered adjunct to the noncovered service, (2) those pathways are followed for most patients receiving the service, and (3) similar patterns of adjunct services occur infrequently with other procedures.